Effects of different botanical oil meal mixed with cow manure organic fertilizers on soil microbial community and function and tobacco yield and quality - Chen, Yuxuan; Lv, Xiaolin; Qin, Yanmin; Zhang, Deping; Zhang, Chaoqun; Song, Zhanfeng; Liu, Dongyang; Jiang, Lianqiang; Huang, Bin; Wang, Jie (Frontiers in Microbiology, 2023)
The continuous application of cow manure in soil for many years leads to the accumulation of heavy metals, pathogenic microorganisms, and antibiotic resistance genes. Therefore, in recent years, cow manure has often been mixed with botanical oil meal as organic fertilizer applied to farmland to improve soil and crop quality. However, the effects of various botanical oil meal and cow manure mixed organic fertilizers on soil microbial composition, community structure, and function, tobacco yield, and quality remain unclear. Therefore, we prepared organic manure via solid fermentation by mixing cow manure with different oil meals (soybean meal, rape meal, peanut bran, sesame meal). Then, we studied its effects on soil microbial community structure and function, physicochemical properties, enzyme activities, tobacco yield and quality; then we analyzed the correlations between these factors. Compared with cow manure alone, the four kinds of mixed botanical oil meal and cow manure improved the yield and quality of flue-cured tobacco to different degrees. Peanut bran, which significantly improved the soil available phosphorus, available potassium, and NO3−-N, was the best addition. Compared with cow manure alone, soil fungal diversity was significantly decreased when rape meal or peanut bran was combined with cow manure, while soil bacterial and fungal abundance was significantly increased when rape meal was added compared with soybean meal or peanut bran. The addition of different botanical oil meals significantly enriched the subgroup_7 and Spingomonas bacteria and Chaetomium and Penicillium fungi in the soil. The relative abundances of functional genes of xenobiotics biodegradation and metabolism, soil endophytic fungi, and wood saprotroph functional groups increased. In addition, alkaline phosphatase had the greatest effect on soil microorganisms, while NO3−-N had the least effect on soil microorganisms. In conclusion, the mixed application of cow manure and botanical oil meal increased the available phosphorus and potassium contents in soil; enriched beneficial microorganisms; promoted the metabolic function of soil microorganisms; increased the yield and quality of tobacco; and improved the soil microecology.